2006
DOI: 10.1002/micr.20257
|View full text |Cite
|
Sign up to set email alerts
|

DNA degradation in nuclei of muscle cells followed by ischemic injury in a rabbit amputation model

Abstract: This study evaluated DNA degradation in nuclei of muscle cells during ischemia in a rabbit limb amputation model. Seven New Zealand rabbits were used. The left rear limb of the animal was amputated. The quadriceps femoris muscle was biopsied, as well as the rabbit carotid arteries. Half of the tissue samples were preserved at a cold temperature (2-4 degrees C), and the other half were kept at room temperature (25 degrees C, global ischemia). Immediately and 4, 8, 12, 16, and 24 h after amputation, muscle tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The motivation for this study was the paucity of information describing outcome information limb amputation for rabbits. A search of the literature identified only limited studies [3][4][5][6][7] involving laboratory rabbits and a single case report 2 of a domestic rabbit with osteosarcoma that did not survive amputation. Only 2 studies 5,7 provided outcome information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation for this study was the paucity of information describing outcome information limb amputation for rabbits. A search of the literature identified only limited studies [3][4][5][6][7] involving laboratory rabbits and a single case report 2 of a domestic rabbit with osteosarcoma that did not survive amputation. Only 2 studies 5,7 provided outcome information.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits were typically euthanized soon after surgery with no evalu-SMALL ANIMALS/ EXOTIC ation of recovery and return to function. 3,4 The purpose of the study reported here was to retrospectively describe morbidity, survival rate, and survival time of client-owned domestic rabbits undergoing amputation of a thoracic or pelvic limb for any reason.…”
mentioning
confidence: 99%
“…From a micro perspective, the occurrence mechanism of muscle atrophy is inseparable from protein metabolism and cell death, therefore blood flow is usually involved in the researches about muscle protein synthesis and degradation or apoptosis. For example, in 2006, Wang et al 80 evaluated DNA degradation in nuclei of muscle cells during ischemia in a rabbit limb amputation model. In 2007, the activation of hypoxia-inducible factor in skeletal muscle cells during ischemia was investigated by Dehne et al 81 A bone marrow cell therapy was performed by Liu et al 82 on a model of severe lower limb ischemia in 2009.…”
Section: Muscle Atrophymentioning
confidence: 99%
“…Las piezas quirúrgicas provenientes de estas intervenciones son procesadas rutinariamente en los servicios de Anatomía Patológica, muchas veces sin las debidas precauciones para conservar este material en condiciones que pudiesen permitir la realización de estudios posteriores con técnicas de biología molecular. Largos períodos de isquemia fría, fijación inadecuada, procesamiento no estandarizado, almacenamiento en condiciones no óptimas, son sólo algunos de los factores que determinan la pérdida de gran cantidad de dicho material [16][17][18] . La ausencia de bancos de tumores en la mayor parte de los servicios asistenciales, también, ha impedido la recolección de tejidos frescos que pudiesen ser utilizados en investigación a nivel genético-molecular.…”
unclassified